PEMETAAN RUANG TERBUKA HIJAU DARI HASIL CITRA LANDSAT 8 MENGGUNAKAN METODE NDVI DI KOTA PADANG - Tri Agung Santoso; Dwi Arini; Fajrin; Dwi Marsiska Driptufany (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The rapid development of Padang City has changed land use, resulting in a reduction in green open space (RTH). To map the distribution of RTH more easily, this study uses remote sensing technology with Landsat 8 OLI satellite imagery. The objective of this study is to identify the availability of RTH in Padang City using the Normalised Difference Vegetation Index (NDVI) on Landsat 8 OLI imagery. According to Indonesian Law No. 26 of 2007, the proportion of RTH in urban areas must be at least 30% of the total urban area, with at least 20% being public RTH and 10% private RTH. Based on the analysis using the NDVI (Normalized Difference Vegetation Index) method from Landsat 8 OLI imagery, it was found that the vegetation condition in Padang City has a relatively high level of greenness, indicating that Green Open Spaces (RTH) still dominate the area. This suggests that Padang City still has RTH areas covering 41,525 hectares or 60%. Green Open Spaces (RTH) in Padang City are distributed across all districts, and based on the analysis, most of these RTH areas are still in good condition, as indicated by a fairly good percentage. However, in the city centre, the availability of RTH is increasingly scarce. Based on the results of this study on calculating the availability of RTH in Padang City in accordance with Law No. 26 of 2007, it was found that.